Personalized warm-up strategies for adult athletes: a meta-analysis based on athletic level, gender, and region - Xu, Ye; Dai, Jianmin; Liang, Xingyue; Zhang, Yurou (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to investigate the acute effects of high-intensity parallel squats (HIPS) on lower-limb explosive power in adult athletes, with a specific focus on how athletic calibre, sex and geographic origin modulate the ensuing potentiation response (PAP/PAPE)—the transient increase in muscular power or performance that follows heavy resistance exercise., and provide evidence for designing precision Warm-up protocols.MethodsFollowing PRISMA guidelines, 58 Randomized controlled trial (973 participants) published in six databases (Web of Science, PubMed, Cochrane, Embase, Scopus, and Ebsco) from 2004 to 2025 were systematically reviewed. Included studies utilized HIPS (≥85% 1RM) as a pre-activation stimulus, with countermovement jump (CMJ), standing long jump (SLJ), and short-distance sprints (10, 20, 30 m et al.) as outcome measures. Effect sizes were pooled using a random-effects model. Subgroup analyses based on athletic proficiency (high-level: squat 1RM/body weight ≥2), gender (male/female), and region (Asian/non-Asian) were conducted, with heterogeneity (I2 statistic) and publication bias (Egger’s test) assessed.ResultsHigh-level athletes exhibited significant CMJ improvement after short and moderate intervals (p ≤ 0.05), whereas low-level athletes showed no gains and even transient inhibition post short intervals (p = 0.08). Non-Asian athletes demonstrated superior CMJ gains after long intervals (>8 min: WMD = 0.86, p = 0.01), while Asian athletes showed no improvement (p = 0.86). Males achieved moderate-interval CMJ enhancement (WMD = 0.95, p = 0.01), whereas females exhibited no significant changes (p = 0.64). In SLJ, low-level (WMD = 5.79, p = 0.01) and non-Asian athletes (WMD = 4.23, p = 0.02) showed gains, but sprint performance remained unaffected across subgroups (p > 0.05). Heterogeneity ranged from low to moderate (I2 = 0–70.6%).ConclusionAthletes with high proficiency (squat 1RM/weight ≥2) can combine short/medium recovery intervals of HIPS warm-up to optimize vertical jump performance; athletes with low proficiency need to prioritize enhancing their basic strength before considering using HIPS for activation to improve acute exercise performance. Males are recommended to rest for 5–8 min after intervention activation and then proceed with training. Non-Asian athletes can attempt a long interval (>8 min) strategy.